Sanitation in Ensenada, Baja California, Mexico: bridging the gap between human rights and practice - García-Searcy, Vanesa; Villada-Canela, Mariana; Muñoz-Pizza, Dalia M. (Frontiers in Water, 2025)
Access to water and sanitation remains a major global challenge and has been prioritized in international sustainable development agendas. In 2015, it was incorporated into the Sustainable Development Goals (Goal 6), aiming for universal and sustainable access by 2030. While water provision often receives more attention due to its immediate impact on quality of life, sanitation is equally relevant for public health and environmental protection. This study examines sanitation in Mexico, focusing on the urban area of Ensenada, Baja California. Despite significant progress in sewer coverage, persistent challenges remain, particularly discrepancies between local and national data that hinder accurate assessment and policy development. Adopting a human rights perspective, this research analyzes technical and social factors affecting access and quality of sanitation services, with a special emphasis on sustainability in wastewater management. A mixed-methods approach—combining documentary research, surveys, and stakeholder interviews—was employed. Results reveal low public awareness of sanitation as a human right, deficiencies in the cleanliness and maintenance of public sanitary facilities, and persistent accessibility barriers for vulnerable populations. Additionally, concerns about septic system failures, wastewater odors (reported daily by 20% of residents), and doubts about treatment effectiveness (expressed by over 65%) were prominent. Nevertheless, the study identifies opportunities for alternative sanitation solutions. Recommendations include infrastructure upgrades, community education initiatives, and continuous monitoring to ensure sustainable, equitable sanitation management, both locally and globally.